First Language Acquisition of Children with Mild Autism: Case Study of Developmental Language Disorders at Palembang Bina Autis Mandiri - Houtman Houtman; Hanni Yukamana; Yenny Puspita (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aimed to determine the language acquisition of autistic children who attended Bina Autism Mandiri (BAM) Palembang. The specific target was to obtain information about an autistic child's language acquisition. The study participant was nine years old when the study was conducted. The research used a descriptive qualitative approach because the analyzed data and results were described in words. The data were obtained based on the speech or language of the autistic child through the employment of proficient and listening methods. The analysis was carried out in three stages; the data reduction stage, the data presentation stage, and the inference stage. Research showed that the study participant could pronounce well. However, the meaning of the words this student wanted to say independently was still limited. This student often repeated the imperative types of speech. This type of narrow imperative appeared only in the categories of requests and prohibitions. The acquisition of the R language, especially the linguistic aspect included in the light group, was still limited. This condition happens because the psychological condition of the student was usually in an uncomfortable state. Painful psychological conditions, for example, being upset and angry, can trigger R to take physical action in the form of beatings and the spoken vocabulary becomes unclear. It can be inferred that the language acquisition of children with autism is much different from that of normal children.